Religious satire in the era of new atheism : do you 'seriously believe that' after 9/11 - Jaffe, Jerry C. (London ; New York : Routledge, 2024)
"Religious Satire in the Era of New Atheism presents a contemporary account of religious satire as evidenced by the modern art of stand-up comedy"--
Instruction: "I survive trauma through my sense of humor" -- Reading between the lines and defining satire: "Seeming seeming" -- Religious satire and doubting Thomases: "I'm here promoting-doubt" -- Acting out the character of God: "Ridiculing the Incarnation" -- comedians satirizing creationists: "I needed to go to this tabernacle of ignorance" -- Conclusion: "People snapped".
Keywords: Religious satire; Atheism; Wit and humor; SOCIAL SCIENCE / Popular Culture; SOCIAL SCIENCE / Sociology of Religion